Students’ attitudes towards South Jakarta’s youth language - Adhitya Reinindra; R. Dian Dia-an Muniroh; Ernie D. A. Imperiani (Passage, 2020)
This study presents the results of a qualitative survey of 56 English Language and Literature study program at Universitas Pendidikan Indonesia. It highlights their attitudes towards the code-switching practices in Bahasa Jaksel. The data were obtained through questionnaire with the students from batch 2015 to 2019 The study employed theories on language attitudes by Crystal (1997) to analyze the data. The findings demonstrated that the students show different attitudes. Overall attitudes of the students were unanimously negative towards the code switching practice in Bahasa Jaksel. The study also found that these attitudes can be related to a number of factors/reasons, i.e. Comprehensibility, appropriateness, language threat, education, intelligence and perception. The findings suggest that the students felt the use of code-switching in South Jakarta is not suitable to be used in real life situations.Keywords: Bahasa Jaksel, code-switching, language attitudes.